DNA Barcoding Analysis Areca Nut from Riau Based on matk Gene - Herman, Herman; Fitriadi, Zul; Jumin, Hasan Basri; Nurbaiti, Nurbaiti; Roslim, Dewi Indriyani (Jurnal Biologi Tropis, 2025)
Areca nut (Areca catechu) is a monocotyledonous plant and belongs to the Arecaceae family. Areca nut trees have an important role in the economic, religious, cultural, and traditional medicine sectors. The use of matK sequence DNA barcodes to identify areca nut species from Riau has never been done before. This study aims to analyze the potential of matK sequences as DNA barcodes for areca nut plants from Riau. Areca nut samples were taken from the Indrigiri Hilir Regency, Riau Province, Indonesia. The samples consisted of five varieties, each represented by seven different individuals. The research stages carried out were fresh leaves colleting, DNA isolation using the Geneaid Mini Plant kit, PCR following Thermo Scientific instructions, agarose gel electrophoresis, sequencing, and data analysis using bioinformatics programs such asBioEdit, BLASTn, and MEGA 11. The results showed that the highest identity value (99.87%) was found in A. catechu (MW785259.1). Six nucleotide variations were found with one critical nucleotide for A. catechu. The matK DNA sequence of areca nut from Riau from this study is the first sequence reported in the GenBank database.